Jean-Luc Nancy on Sovereignty and the Retreat of the Christian God (Res Publica. Revista de Historia de las Ideas Políticas, 2014)
this paper explores the relationship between sovereignty and the death of god in the work of Jean-luc Nancy. By connecting Nancy’s comments on sovereignty to his project on the Deconstruction of Christianity, it explores how the metaphysical assumption of the sovereign, in the form of god, king, or law, can never subsume the excess of sovereignty. By situating Nancy’s work in relation to Carl Schmitt and georges Bataille, it argues that sovereignty evades the grasp of any sovereign proclares mation. additionally, the analysis shows how Nancy’s interpretation of sovereignty appeals neither to a mythos, nor to nothingness, as a foundation. for Nancy, sovereignty is not a foundation but a mark, or trace, of the nothingness that unseats every sovereign foundation. What is therefore offered in this paper, is a reading of sovereignty as passage and trace, in which negation is not a foundation but an opening that makes way for each singular gesture of creation.